Muscle wasting diseases has two distinct trajectories on the 3‐dimensional age‐BMI‐peak VO2 scatterplot. Issue 2 (1st July 2018) - Sugie, Masamitsu; Harada, Kazumasa; Takahashi, Tetsuya; Nara, Marina; Koyama, Teruyuki; Fujimoto, Hajime; Kyo, Shunei; Ito, Hideki
Abstract: Aims: Frailty and sarcopenia are age‐related morbid states, and a low body mass index (BMI) is a characteristic of frailty and cachexia. However, no common index for assessing these three muscle wasting states is available, making it difficult to understand the relationship among them. Peak oxygen uptake (peak VO2 ), an index of life expectancy, may be a useful common index. Therefore, this study aimed to investigate the relationship among sarcopenia, frailty, and cachexia using age, BMI, and peak VO2 . Methods and Results: Participants were 175 Japanese community dwelling older adults (58 men, 117 women; 77.6 years). We assessed biochemical, physiological, and physical factors, and symptoms associated with frailty, and cachexia. Peak VO2 was assessed with a cardiopulmonary exercise test. Participants were classified into five groups: robust, pre‐frail, frail, sarcopenia, and cachexia. We compared the groups by age, BMI, and peakVO2 with average values and 95% confidence intervals (CIs). 17% (n=30) of participants were classified as robust, 40% (n=70) as pre‐frail, 12% (n=21) as sarcopenia, 25% (n=44) as frail, and 6% (n=10) as cachexia. Significant differences were found in age (robust vs. frail, pre‐frail vs. frail), BMI (robust vs. cachexia, pre‐frail vs. cachexia, frail vs. cachexia), and peak VO2 (robust vs. frail, robust vs. cachexia, pre‐frail vs. cachexia) with average values and 95% CIs. Three dimensions among age, BMI and peak VO2 revealed two trajectories (from robust to frailty via pre‐frailty, and from robust to cachexia via sarcopenia) among muscle wasting diseases. Conclusions: This study revealed two trajectories among muscle wasting diseases.